Resolution refutation help

  1. 1. The problem statement, all variables and given/known data

    (a) Give a resolution refutation of the following formula:
    (x ∨ y) ∧ (y ∨ ¬z ∨ ¬x) ∧ ¬x ∧ (¬y ∨ x)

    (b) Convert the formula into CNF and give a resolution refutation for it:
    x1 ∧ (x1 ↔ x2) ∧ (x2 ↔ x3) ∧ (x3 →¬ x1)


    2. Relevant equations

    n/a

    3. The attempt at a solution

    I need help with basic Resolution Refutation. If someone could walk me through it, or give an easier explanation then the one my prof tried to give that would be greatly appreciated
     
  2. jcsd
Know someone interested in this topic? Share a link to this question via email, Google+, Twitter, or Facebook

Have something to add?

0
Draft saved Draft deleted